Compliance level difference of tele-exercising obese office employee on body weight and body fat - Kuswari, Mury; Rimbawan, Rimbawan; Hardinsyah, Hardinsyah; Dewi, Mira; Gifari, Nazhif (Journal Sport Area, 2022)
The problem of overnutrition and obesity tend to increase year by. Office employee are susceptible to physical inactivity and obesity. In context of current pandemic, exercising via online media, termed ‘tele-exercise’ may be an effective alternative intervention. However, the effect of compliance and timing of exercise on overall health-related output are still not often discussed. The purpose of the study is to compare the effect of tele-exercise done during working hours vs. after working hours on obese office employee’s weight loss and improvement of body fat percentage, as well as their relation to compliance level. The design of this study is quasi-experimental design, with obese office employee as participants, which then grouped into after work exercise (AW, n = 36, 1-hour duration) and mid-work exercise (DW, n = 21, 30-minute duration). Total sampling was used since the target population were under 100 people. Exercises were done 3 times/week for 12 weeks. Data collected were sample characteristics, bodyweight, and percentage of body fat. Both timing of intervention is effective on reducing body weight significantly (p<0.05). Significant reduction (p<0.05) on percentage of body fat is only occurring in DW group. Compliance level for AW and DW group are 63.75% and 61.23%, respectively, and being insignificant to each other (p>0.05). The contribution of compliance in shorter exercise/DW on body fat loss and weight loss is 23.1% and 20.9%, respectively; while the contribution of compliance in longer exercise/AW is 11.3% on body weight loss. A short, mid-working exercise have the similar or even better effect than 1-hour after-work exercise session on weight loss and body fat loss. We recommend tele-exercising during working hours for at least 30 minutes to achieve significant body weight and body fat loss.